2022
DOI: 10.1002/glia.24190
|View full text |Cite
|
Sign up to set email alerts
|

A unique cerebellar pattern of microglia activation in a mouse model of encephalopathy of prematurity

Abstract: Preterm infants often show pathologies of the cerebellum, which are associated with impaired motor performance, lower IQ and poor language skills at school ages. Using a mouse model of inflammation-induced encephalopathy of prematurity driven by systemic administration of pro-inflammatory IL-1β, we sought to uncover causes of cerebellar damage. In this model, IL-1β is administered between postnatal day (P) 1 to day 5, a timing equivalent to the last trimester for brain development in humans.Structural MRI anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 112 publications
1
10
0
Order By: Relevance
“…Recurrent neuroinflammation was associated with metabolic disorders following perinatal inflammation in the long term. Research has established that perinatal inflammatory events lead to pronounced and diffuse microgliosis in the acute phase [14, 16, 18]. It is noted that our study showed recurrent microgliosis accompanied by neuron loss in the ARC of the hypothalamus and multiple altered metabolic signaling pathways of microglia in the middle-aged IL-1β male group.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Recurrent neuroinflammation was associated with metabolic disorders following perinatal inflammation in the long term. Research has established that perinatal inflammatory events lead to pronounced and diffuse microgliosis in the acute phase [14, 16, 18]. It is noted that our study showed recurrent microgliosis accompanied by neuron loss in the ARC of the hypothalamus and multiple altered metabolic signaling pathways of microglia in the middle-aged IL-1β male group.…”
Section: Discussionsupporting
confidence: 50%
“…Paired-end sequencing was performed on Illumina’s NovaSeq 6000 sequencing system. The analyses were performed using the Eoulsan pipeline, including read filtering, mapping, alignment filtering, read quantification, normalization, and differential analysis as previously described by [18, 23]. StringTie was used to perform mRNA expression levels by calculating FPKM [24].…”
Section: Methodsmentioning
confidence: 99%
“…In addition to differences in distributions of the microglia described above, there are regional differences in the basal state of the microglia transcriptional profile, most well established in the grey matter versus the white matter, within regions and in adult studies of disease (Amor et al, 2022 ; Spencer et al, 2019 ; van der Poel et al, 2019 ). However, transcriptomic profiling of microglia in the cerebrum and the cerebellum in an inflammation‐induced model of EoP demonstrated a common reactive signature characterized by an over‐representation of Gene Ontology terms related to inflammation and cell proliferation (Klein et al, 2022 ). Further analysis revealed a specific cerebellar signature with significant enrichment of interferon (IFN) signaling, particularly type II IFN (IFN‐γ) signaling following systemic inflammatory exposure, which was not significantly observed in the microglia of the cerebrum.…”
Section: Glial Cells and Mechanismsmentioning
confidence: 99%
“…Systemic inflammation in the mouse results in a region-specific volume reduction of both cerebellar white and grey matter ( Klein et al, 2022 ). These cerebellar volume deficits were associated with enrichment of pro-inflammatory markers in microglia, reduced proliferation of oligodendrocyte progenitors, and reduced levels of myelin basic protein and myelin-associated glycoprotein that affected myelination in the neonatal cerebellum ( Cardoso et al, 2015 ; Klein et al, 2022 ).…”
Section: Adverse Effects Of Other Factors Commonly Associated With Pr...mentioning
confidence: 99%
“…Systemic inflammation in the mouse results in a region-specific volume reduction of both cerebellar white and grey matter ( Klein et al, 2022 ). These cerebellar volume deficits were associated with enrichment of pro-inflammatory markers in microglia, reduced proliferation of oligodendrocyte progenitors, and reduced levels of myelin basic protein and myelin-associated glycoprotein that affected myelination in the neonatal cerebellum ( Cardoso et al, 2015 ; Klein et al, 2022 ). A similar pattern of microglia activation in the cerebellum was observed in preterm sheep in which intravenous injection of a low dose of Escherichia coli lipopolysaccharide (LPS) led to an increased number of microglia, cerebellar white matter injury, and loss of oligodendrocytes ( Baburamani et al, 2014 ; Dean et al, 2014 ).…”
Section: Adverse Effects Of Other Factors Commonly Associated With Pr...mentioning
confidence: 99%